Republished: Bacterial proteases in IBD and IBS. Issue 1047 (17th December 2012) - Steck, Natalie; Mueller, Kerstin; Schemann, Michael; Haller, Dirk
Abstract : Proteases play a decisive role in health and disease. They fulfil diverse functions and have been associated with the pathology of gastrointestinal disorders such as inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS). The current knowledge focuses on host-derived proteases including matrix metalloproteinases, various serine proteases and cathepsins. The possible contribution of bacterial proteases has been largely ignored in the pathogenesis of IBD and IBS, although there is increasing evidence, especially demonstrated for proteases from pathogenic bacteria. The underlying mechanisms extend to proteases from commensal bacteria which may be relevant for disease susceptibility. The intestinal microbiota and its proteolytic capacity exhibit the potential to contribute to the pathogenesis of IBD and IBS. This review highlights the relevance of host- and bacteria-derived proteases and their signalling mechanisms.